Penggunaan pupuk subsidi dalam menekan biaya produksi dan pengaruhnya terhadap pendapatan petani di kecamatan Tanjung Lago - Larasati, Agnes; Antoni, Mirza; Lifianthi, Lifianthi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study analyzes the effect of the use of subsidized fertilizer in reducing production costs and its effect on the income of lowland rice farming in Tanjung Lago District. The use of subsidized fertilizers as a factor of production in addition to increase productivity is also expected to reduce production costs and can affect the income of rice farmers. The approach model in this research is statistical analysis. The results showed that the use of subsidized fertilizers reduced production costs by 5% and affected the income of rice farmers in Tanjung Lago District. For one hectare of land at the same time during the planting season, farmers who receive 3 types of subsidized fertilizers earn an average of Rp. 21.913.710, - and for farmers who receive 2 types of subsidized fertilizer, the average income reaches Rp. 14.411.540, - with the percentage difference in income reaching 34%. This difference in income is not only influenced by the suppression of production costs from inputs using subsidized fertilizers but is also influenced by farmers' income due to differences in production results.